1992
DOI: 10.1017/s0022215100118481
|View full text |Cite
|
Sign up to set email alerts
|

The histology of ‘stored’ autologous ossicles

Abstract: Controversy still exists concerning the ultimate fate of transposted or transplanted ossicles in tympanoplasty. Histological studies on autologous and homologous ossicles removed at revision operations, or from animal studies, vary in their conclusions. The viability, of such materials used in the long-term is still uncertain. Whether this has any functional significance is also uncertain.This report contains a histological review of 10 ossicle remnants stored in the ‘closed’ mastoid cavity for 12 months, foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
2
5
0
Order By: Relevance
“…It would make sense that complete removal of the cholesteatoma and replacement of the ossicle in a favorable environment may reverse the inflammatory process. This concept is consistent with the findings of Wake et al 9 In their study, ossicle remnants, which were removed during closed cavity mastoidectomy, were stored in the mastoid cavity after thorough cleaning. All these ossicle remnants, when removed 12 months later in a “second‐look” operation, were found to have remained viable.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…It would make sense that complete removal of the cholesteatoma and replacement of the ossicle in a favorable environment may reverse the inflammatory process. This concept is consistent with the findings of Wake et al 9 In their study, ossicle remnants, which were removed during closed cavity mastoidectomy, were stored in the mastoid cavity after thorough cleaning. All these ossicle remnants, when removed 12 months later in a “second‐look” operation, were found to have remained viable.…”
Section: Discussionsupporting
confidence: 91%
“…The two studies that reported no residual disease using methods other than autoclaving were too small (10 specimens in both series) to be conclusive. 8,9 In one of these studies, 9 the histological examination was probably suboptimal because only 15 slides were examined from each sectioned ossicle. In the present study, histological sections were at 4 μm through the entire ossicle, which meant 800 or more sections for a single minimally eroded incus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These features would necessarily preclude the use of autograft ossicles in cholesteatomatous ears. However, others (Seifi and Fouad, 1992;Wake et al, 1992) have not noted similar findings. Such conflicting reports prompted us to study histologically a series of ossicles from cholesteatomatous ears and also determine whether there is any correlation between the appearance of the ossicle under the surgical operating microscope and its histological appearance.…”
Section: Introductionmentioning
confidence: 87%
“…The use of autograft ossicles in middle ear reconstruction was first reported by Hall and Rytzner (1957). Several studies on the use of autologous ossicles in tympanoplasty followed (Hall and Rytzner, 1960;Kerr and Smyth, 1971;Lang et al, 1986;Lang et al, 1989;Wake et al, 1992). One of the problems with the use of autograft ossicles in cholesteatomatous ear disease is that ossicular erosion due to the disease process itself limits its availability for reconstruction.…”
Section: Introductionmentioning
confidence: 99%